Effect of Change Management on Employee Performance in Nepalese Commercial Banks - Ms. Samikshya Prasai (HM Journals, 2025)
Purpose: The study intends to analyze the effect of change management on employee performance in commercial banks. Method: Data collection meticulously employed a simple random sampling technique. Data is collected from 300 bank employees via adopted questionnaire on a 7-point Likert scale. 240 complete responses received, yielding an 80% response rate. Descriptive and causal-comparative research design utilized with independent sample t-test, one-way ANOVA, Mann-Whitney U test, Krushkal-Wallis H Test, correlation, and regression analysis. Findings: Beta coefficients indicate higher influence of Change in organizational structure on employee performance. Implications: It is recommended that organizations should reformulate their policies and strategies promoting supportive work culture, clear guidelines regarding roles and responsibilities, fostering a culture of transparency and communication to enhance employee commitment. Managers should provide support to increase satisfaction and better employee morale.